(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the QT dispersion for coronary artery disease in cardiac stress test by transesophageal atrial pacing in patients with coronary heart disease. Study Design: Comparative study. Place and Duration of Study: This study was conducted at the Cardiology Department, Mayo Hospital, Lahore, Punjab Institute of Cardiology and Umar Cardiac Center, Lahore from January 2015 to August 2015. Materials and Methods: Fifty consecutive inpatients underwent cardiac stress testing (CST) by TEAP firstly, and then accepted selective coronary arteriography (SCA). These patients were suspected to have coronary heart disease (CHD), 28 were positive (CAD) and 22 were negative, normal coronary group (NCA), as control group. Measurements of QTd in two groups before and after CST were analyzed in and between groups. Results: QTd was high in CAD than NCA group at baseline or every stages after CST (P<O.05, 0.01); QTd instantly and 2mm after CST was significantly greater than before CST in CAD group, but QTd 4mm and 6mm after CST dropped by the baseline . In NCA group, there were no differences of QTd measurements to be observed before and every stage after CST. Measurement of QTd immediately or 2mm after CST ( 6Oms: positive) with the sensitivity (80.5%), specificity (90.4%), positive predictive value (91. 5%), negative predictive value (81.O %) and accuracy (85.5%). Conclusion: Patients with CAD have greater QTd than normal subjects; and QTd increased further in CAD during CST by TEAP, whereas, NCA group with no significant change.